Integrating a novel shape memory polymer into surgical meshes decreases placement time in laparoscopic surgery: An in vitro and acute in vivo study. Issue 9 (30th July 2013) - Zimkowski, Michael M.; Rentschler, Mark E.; Schoen, Jonathan; Rech, Bryan A.; Mandava, Nageswara; Shandas, Robin
Abstract : About 600, 000 hernia repair surgeries are performed each year; recently, the use of laparoscopic minimally invasive techniques has become increasingly popular in these operations. Use of surgical mesh in hernia repair has shown lower recurrence rates compared to other repair methods. However in many procedures, placement of surgical mesh can be challenging and even complicate the procedure, potentially leading to lengthy operating times. Various techniques have been attempted to improve mesh placement, including use of specialized systems to orient the mesh into a specific shape, with limited success and acceptance. In this study, a programmed novel Shape Memory Polymer (SMP) was integrated into commercially available polyester surgical meshes to add automatic unrolling and tissue conforming functionalities, while preserving the intrinsic structural properties of the original surgical mesh. Tensile testing and Dynamic Mechanical Analysis was performed on four different SMP formulas to identify appropriate mechanical properties for surgical mesh integration. In vitro testing involved monitoring the time required for a modified surgical mesh to deploy in a 37°C water bath. An acute porcine model was used to test the in vivo unrolling of SMP integrated surgical meshes. The SMP‐integrated surgical meshes produced an automated, temperature activated, controlled deployment of surgical mesh on the order of several seconds, via laparoscopy in the animal model. Results indicate surgical mesh modified with SMP is capable of laparoscopic deployment in vivo, activated by body temperature. This suggests a reduction in surgical operating time and improved mesh placement characteristics is possible with SMP‐integrated surgical meshes. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2613–2620, 2013.